Controlling the Controllers: Regulation of Histone Methylation by Phosphosignalling. Issue 12 (December 2020) - Separovich, Ryan J.; Pang, Chi Nam Ignatius; Wilkins, Marc R.
Abstract : Histone methylation is central to the regulation of eukaryotic transcription. Here, we review how the histone methylation system itself is regulated. There is substantial evidence that mammalian histone methyltransferases and demethylases are phosphorylated and regulated by upstream signalling pathways. Functional studies of specific phosphosites are revealing which kinases and pathways signal to the histone methylation system and are discovering the diverse effects of phosphorylation on enzyme function. Nevertheless, the majority of phosphosites have no known kinase or function and our understanding of how histone methylation is regulated is fragmentary. Improved approaches are needed to establish and study the key regulatory phosphorylation sites on histone methyltransferases and demethylases, to avoid focus on constitutive sites which may have little regulatory purpose. Highlights: Histone methylation is an important epigenetic modification that controls eukaryotic transcription, and its dysregulation contributes to the aetiology of human disease. Recent phosphoproteomic studies have revealed that mammalian histone methyltransferase and demethylase enzymes are extensively phosphorylated. Kinases that phosphorylate histone methyltransferase and demethylase enzymes are from many different signal transduction pathways, however, most phosphosites have no known kinase. Phosphorylation has diverse effects on histone methyltransferase and demethylase biology, affecting their catalytic activity, chromatin binding, and degradation. Targeted studies have investigated a tiny proportion of phosphorylation sites, meaning that our understanding of how the intracellular signalling network connects with histone-based gene regulatory systems is rudimentary.